Geological Interpretation of the Abu Jir Fault Zone between Hit and Kubaisa areas using a 2D Electrical resistivity imaging technique - Rajab, Omama Talaat; Ali, Kamal Kareem; AL-Menshed, Firas H. (Iraqi Journal of Science, 2026)
The two-dimensional Electrical Resistivity Imaging (ERI) technique was used in this study to investigate The variations in resistivity within the Hit-Kubaisa area, Abu Jir Fault Zone (AJFZ) to detect fractures zone and evaluation of this technology in detecting faults. The study also aims to analyze the impact of these fractures on the geology of the region. Using the Wenner-Schlumberger array, the researchers conducted four survey lines with 120 electrodes spaced 10 meters apart, allowing them to map subsurface geological structures down to a depth of 240 meters. The results showed clear differences in resistivity, making identifying fracture zones and potential subsurface cavities possible. It also highlighted how these faults affect the sedimentary layers, especially the differences in the thickness of the Euphrates Formation and the absence of the Ana Formation.